Effect of Different Substrates and Supplements in Production of Pleurotus ostreatus in Dang, Nepal - Thakur, Gaurav; Neupane, Shiva; Shrestha, Suraj; Acharya, Basistha (Agriculture Development Journal, 2024)
An investigation was laid out to evaluate the production of Pleurotus ostreatus on different substrates and supplements in inner Terai of Nepal, Dang, Deukhuri. Ten different treatments with different substrates and supplements were tested in completely randomized design, replicated four times during the spring season with an average daily temperature of 20-27° C and relative humidity ranging from 80-95 %. The parameters taken for the observation during the experiment were spawn run period, length of stalk, diameter of stalk, diameter of pileus, thickness of pileus, fresh weight of mushroom, ash content, moisture content and biological efficiency of treatments. The research revealed that there were statistically significant yield differences associated with rice straw + banana leaves + rice bran (2.46 kg/ball), followed by rice straw + chickpea flour (2.35 kg/ball). The spawn run duration (23 days) was shortest in banana leaves with highest stipe length (5.01cm). The biological efficiency of various mixtures was found between 40 to 159%, the highest being in treatment rice straw + banana leaves + rice bran and followed by rice straw + chickpea flour. Highest moisture percentage (89.4%) was recorded in rice straw + maize flour. It was accomplished that rice straw + banana leaves whenever abundantly present, can be reasonably used in mixtures with rice bran supplement for better mushroom cultivation. Thus, its use is suggested to farmers in this country where large volumes of rice bran and dry banana leaves are discarded as agricultural residue.